2023
DOI: 10.1002/2688-8319.12226
|View full text |Cite
|
Sign up to set email alerts
|

Ungulate occurrence in forest harvest blocks is influenced by forage availability, surrounding habitat and silviculture practices

Abstract: Forest harvesting causes habitat loss and alteration and can change predator–prey dynamics. In Canada, forest harvesting has shifted the distribution and abundance of ungulates (deer, elk and moose) that prefer early seral forest, resulting in unsustainable caribou predation by shared predators (bears, cougars and wolves). Long‐term solutions for caribou recovery require management to reduce ungulate prey species within caribou ranges. Silviculture practices applied after forest harvesting directly affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…During winter, as previously mentioned, pipelines likely offer less shelter, cover, and forage available above the snowpack than seismic lines, which is likely driving winter moose selection for pipelines only when other linear features are not available to them. At the fine scale, we found that moose were indifferent to pipelines regardless of the surrounding habitat or underlying soil wetness but that there were differences among individuals, and therefore, like seismic lines and harvest blocks, moose use of pipelines is most likely linked to finer scale characteristics like vegetation composition, lateral cover, and the presence of game trails (McKay & Finnegan, 2023;Tattersall et al, 2023).…”
Section: Populationmentioning
confidence: 87%
See 2 more Smart Citations
“…During winter, as previously mentioned, pipelines likely offer less shelter, cover, and forage available above the snowpack than seismic lines, which is likely driving winter moose selection for pipelines only when other linear features are not available to them. At the fine scale, we found that moose were indifferent to pipelines regardless of the surrounding habitat or underlying soil wetness but that there were differences among individuals, and therefore, like seismic lines and harvest blocks, moose use of pipelines is most likely linked to finer scale characteristics like vegetation composition, lateral cover, and the presence of game trails (McKay & Finnegan, 2023;Tattersall et al, 2023).…”
Section: Populationmentioning
confidence: 87%
“…During summer, the width of pipelines combined with ongoing vegetation management may result in pipelines having similar thermal cover, but less forage availability than harvest blocks and wildfires, making pipelines less attractive to moose when harvest blocks and wildfires are available. Moose use of harvest blocks and pipelines during summer is linked to the availability of shrubs and lateral cover (McKay & Finnegan, 2023;Tattersall et al, 2023); pipelines are periodically cleared to maintain line-of-sight (Alberta Energy Regulator, 2016;MacDonald et al, 2020), while with the exception of mechanical or chemical stand tending a few years after planting, harvest blocks are left to regenerate. Therefore, harvest blocks and areas that are naturally regenerating after wildfires are likely more attractive sources of shrub and sapling moose forage than maintained pipelines with graminoids and clover less preferred by moose (MacDonald et al, 2020;McKay & Finnegan, 2023;Tattersall et al, 2023).…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Young harvest areas in the GVE are primarily composed of regenerating deciduous trees and dense understory vegetation (primarily aspen), which probably provide ideal forage conditions for adult deer and hiding cover for fawns (Courtois et al, 2002; Rohm et al, 2007). Indeed, studies from other parts of the boreal forest have demonstrated that deer often select for recently‐harvested areas during summer (Lesage et al, 2002; McKay & Finnegan, 2023). Although these patches of high‐quality habitat may have benefits for both adult and neonatal ungulates, wolves appear to exploit deer concentrated in them.…”
Section: Discussionmentioning
confidence: 99%